FDI and Economic Growth: An Endogenous Nexus and the Risk of Foreign Capitalisation in the Coastal Region of China - Chen, Chunrong (2008)
This study focuses on the dynamic relationship between inward FDI and economic growth in the coastal region of China. Three sets of empirical models are developed to examine the two main hypotheses of FDI-led growth and growth-driven FDI, as well as the crowding in effect, which are based on a sample of 9 provinces panel data during 1995 and 2007 (117 observations). By using the fixed effects estimation, the results confirm essential findings of earlier studies on the positive nexus of FDI and economic growth and provincial heterogeneity across the coastal region of China. However, the interaction term of FDI and human capital is disapproved in the study, in spite of schooling factor yielding favourable values. In addition, empirical results suggest that FDI is an important vehicle for inducing domestic investment instead of detracting it. Finally, constructive recommendations for the local government and multinational enterprises are provided on the basis of findings and risk capitalisation issues.